1999
DOI: 10.1073/pnas.96.19.10695
|View full text |Cite
|
Sign up to set email alerts
|

Toward the bilayer proteome, electrospray ionization-mass spectrometry of large, intact transmembrane proteins

Abstract: Genes encoding membrane proteins comprise a substantial proportion of genomes sequenced to date, but ability to perform structural studies on this portion of the proteome is limited. Electrospray ionization-MS (ESI-MS) of an intact protein generates a profile defining the native covalent state of the gene product and its heterogeneity. Here we apply ESI-MS technology with accuracy exceeding 0.01% to a hydrophobic membrane protein with 12-transmembrane ␣-helices, the full-length lactose permease from Escherichi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
103
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(106 citation statements)
references
References 31 publications
3
103
0
Order By: Relevance
“…For ESI-MS under denaturing conditions, the salt-containing samples were diluted with formic acid (90 l of 90% formic acid; Fisher Scientific, Fair Lawn, NJ; ACS reagent grade), vortexmixed for 1 min, and immediately injected onto an HPLC system for online liquid-chromatography mass spectrometry (LC-MS). A gel-filtration column [SW2000 XL; Tosoh Biosciences; chloroform/methanol/1% formic acid in water, 4/4/1 (vol/vol/vol); 250 l/min; 40°C] was used to desalt the sample and provide highly denaturing conditions (7,34). Column eluent was directed to an ion-spray source of a triple-quadrupole mass spectrometer (API IIIϩ; PE Sciex/Applied Biosystems, Foster City, CA) tuned and calibrated as described in ref.…”
Section: Methodsmentioning
confidence: 99%
“…For ESI-MS under denaturing conditions, the salt-containing samples were diluted with formic acid (90 l of 90% formic acid; Fisher Scientific, Fair Lawn, NJ; ACS reagent grade), vortexmixed for 1 min, and immediately injected onto an HPLC system for online liquid-chromatography mass spectrometry (LC-MS). A gel-filtration column [SW2000 XL; Tosoh Biosciences; chloroform/methanol/1% formic acid in water, 4/4/1 (vol/vol/vol); 250 l/min; 40°C] was used to desalt the sample and provide highly denaturing conditions (7,34). Column eluent was directed to an ion-spray source of a triple-quadrupole mass spectrometer (API IIIϩ; PE Sciex/Applied Biosystems, Foster City, CA) tuned and calibrated as described in ref.…”
Section: Methodsmentioning
confidence: 99%
“…We note that other potential applications of our direct proteoliposome nano-ESI-MS technique lie in the field of proteomics of membrane proteins (29), which are difficult to characterize because of their inherent insolubility in aqueous solutions as well as the fact that membrane protein-solubilizing detergents cannot easily be used in nano-ESI-MS. Moreover, this technique could be exploited in the investigation of lipid membrane structures by direct introduction of, for instance, plasma membrane vesicles or detergent-resistant membrane vesicles (30).…”
Section: Esi Ms͞msmentioning
confidence: 99%
“…An aliquot (100 g) was wetted with 10 l of water and dissolved in 90 l of undiluted formic acid (90%, v/v) prior to immediate injection onto a size exclusion chromatography HPLC system (Super SW2000, Tosoh Biosciences, Montgomeryville, PA) equilibrated in a buffer containing chloroform, methanol, 1% formic acid in water (4:4:1, v/v/v) at 250 l/min and 40°C (13,18) to purify the bacteriorhodopsin away from small molecule contaminants including lipids and CHAPS. Eluent was directed to the standard electrospray ionization source of the LTQ-FT Ultra mass spectrometer (Ionmax) with the flow dropped manually to 10 l/min as the UV absorbance exceeded 50 milliabsorbance units at the start of the first peak containing the protein.…”
Section: Protein Samplesmentioning
confidence: 99%
“…Previously, it was demonstrated that a variety of integral membrane proteins could be analyzed by ESI-MS on low resolution analyzers with mass accuracy similar to that achievable for soluble proteins (4,13). Subsequently, top-down mass spectrometry was performed on small integral subunits of the cytochrome b 6 f complex using quadrupole time-of-flight analyzers (14), and FT-MS was used for the first time on bacteriorhodopsin apoprotein, achieving mass accuracy Ͻ10 ppm (15).…”
mentioning
confidence: 99%